Analysis of Longitudinal and Survival Data: Joint Modeling, Inference Methods, and Issues. (7th December 2011) - Wu, Lang; Liu, Wei; Yi, Grace Y.; Huang, Yangxin
Abstract : In the past two decades, joint models of longitudinal and survival data have received much attention in the literature. These models are often desirable in the following situations: (i) survival models with measurement errors or missing data in time-dependent covariates, (ii) longitudinal models with informative dropouts, and (iii) a survival process and a longitudinal process are associated via latent variables. In these cases, separate inferences based on the longitudinal model and the survival model may lead to biased or inefficient results. In this paper, we provide a brief overview of joint models for longitudinal and survival data and commonly used methods, including the likelihood method and two-stage methods.